How to outrun a crocodile when your shoes are untied - Keating, Jess (Sourcebooks Inc, 2014)
When twelve-year-old Ana's zoologist parents move the whole family into the zoo, the Sneers--the clan of carnivorous female predators in her class--have even more ammunition to make her life miserable, although she tries to act like a chameleon and fade into the background.